The existence on great Sheikh Muhyiddin Ibn al-Arabi | الجانب الوجودي عند الشيخ الأكبر محيي الدين ابن العربي - Muhammad Yunus Masruhin (Al-Zahra : Journal for Islamic and Arabic Studies, 2010)
As a great thinker, the author of the book "al-Futuhat al-Makkiyah", Ibn al-Arabithougnt's caused pro and contra.this research try to reach the concept of Ibn alArabibased on the legality of epistemology and certain study strategy. thisstudy conducted by reading biography of llin al-Arabi in case of typography,viewing some his dialogue about concept of sufism that mentionea in somebooks, such as dialogue about existence and time, dichotomy of sufism identity(Sharia vs haqiqa),and fictitious experience of Ibn al-Arabi. by this method, theconcept of al-as ma' al-mujarrad (Allan) including all of asma al-husna,transfiguration of Allah and the compatibility time t:fiat can represent the holyindividual personification -according to sufism-, are becoming acceptable,rational and possible thing.